2016
DOI: 10.1007/s10118-016-1810-8
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties and hydrogen bonds of mono-functional polybenzoxazines with different N-substituents

Abstract: A series of mono-functional benzoxazine monomers with different N-substituents were synthesized from phenol, formaldehyde, and various amines (ammonia, methylamine, n-butylamine, dodecylamine), named P-am, P-m, P-b, and P-da, respectively. The surface properties of these polybenzoxazine films were proven by contact angle measurements. The hydrogen bond network of the polybenzoxazine systems was studied using the FTIR spectra. And the results showed that the surface free energy increased with increasing the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
(18 reference statements)
4
16
0
Order By: Relevance
“…It can be attributed to the fact that with the ring-opening of oxazine rings, the formation of H-bonds between intramolecular and intermolecular chains increased. This trends were well consistent with the published literatures [41,42].…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…It can be attributed to the fact that with the ring-opening of oxazine rings, the formation of H-bonds between intramolecular and intermolecular chains increased. This trends were well consistent with the published literatures [41,42].…”
Section: Resultssupporting
confidence: 94%
“…The characteristic absorption observed at around 3289–3555 cm −1 can be mainly assigned to the intermolecular and intramolecular H-bonds, which were formed between the hydroxyl and nitrogen atoms generated from the ring-opening polymerization of oxazine rings [39,40]. As the references reported that the intramolecular H-bonds could turn into intermolecular H-bonds when the temperature went on which contributed to the increase of surfce free energy of cured matrix [41,42]. It was well known that the formation of hydrogen bonds was sensitive to temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophilicity of the DBD-POXI modified membranes can be attributed to the polar carbonyl groups. In addition, nucleophilic attack on DBD could occur on the carbonyl group, generating a -OH group, which would contribute to the hydrophilicity [44][45][46]. Figure 6.…”
Section: Crosslinking Of Poxi Membranesmentioning
confidence: 99%
“…It is known that, in addition to the chemical structures, the hydrogen bonds present in the polyoxazines also play an important role in a wide variety of properties of these compounds. A number of studies have observed the existence of bonds of the type -OH⋯O, -OH⋯N, and -OH⋯π in poly(oxazines) and demonstrated that such bonds contribute to the improvement of their thermal properties, such as elevated glass transition temperatures [18][19][20]. Thus, the insertion of groups that promote the formation of these bonds in polyoxazine compounds is also a strategy for obtaining materials with improved properties.…”
Section: Introductionmentioning
confidence: 99%